The nature and extent of the literature on linked reproductive health datasets in the UK: a scoping review - Hall, Jennifer; Harvey-Pescott, Lois; Ko, Sum Yue (Jessica); Stevens, Rose; Pathak, Neha; Ali, Ifra; Barrett, Geraldine; Shand, Jenny; Dickson, Kelly (International Journal of Population Data Science, 2025)
Introduction Data linkage methodologies are increasingly being utilised across research, but there is currently no evidence on the extent and nature of studies that have used linked reproductive health data. The objective of this scoping review is to identify UK studies that use reproductive health data linkage, to improve our understanding of how data linkage could be used for policy, practice, and research in reproductive health. Methods We conducted a scoping review using a systematic search in five databases: MEDLINE, EMBASE, CINAHL, MIDIRS, and PSYCINFO to identify literature published in English between January 2000 – April 2024. Following duplication removal, piloting, and screening of titles/abstracts, screening of full texts was conducted. Publications using reproductive health data linkage among UK participants of reproductive age were included. Data was extracted from included articles to capture details relating to study characteristics and what, how, and why data was linked. Findings Of the 7,291 identified studies, 272 studies were included in the review. Most studies using data linkage answered questions around reproductive cancer and maternal and child health, whilst only a few studies focused on abortion, contraception, menopause, and preconception health. Several nationally agreed reproductive health indicators did not appear in any included study. Information on sample sociodemographic characteristics, such as ethnicity and deprivation, was often unreported, limiting the identification of health inequalities. Many different datasets were linked (n = 155) with routine health data sources, such as hospital episode statistics (HES), being the most frequently linked. Interpretation There is a growing body of research using linked UK reproductive health data, with gaps in which reproductive health domains are covered and which sample characteristics are reported. Further efforts to create a comprehensive, linked reproductive health data resource with robust linkage methods would enable us to fill data gaps, examine inequalities, and explore reproductive health trajectories. Funding National Institute for Health and Care Research (NIHR) Policy Research Unit in Reproductive Health.